Relationship between liver and cardiometabolic health in type 1 diabetes - Tas, Emir; Vu, Bach-Mai Katherine; Mendizabal, Brenda; Libman, Ingrid; Muzumdar, Radhika (Frontiers in Endocrinology, 2024)
Introduction: Type 1 diabetes (T1D) is a chronic condition marked by insulin deficiency and hyperglycemia, with an increasing global incidence, particularly among children. Despite improvements in diabetes management, individuals with T1D continue to experience higher rates of cardiovascular disease (CVD), the leading cause of mortality in this population. Traditional CVD risk factors such as dyslipidemia and poor glycemic control are insufficient to fully explain the elevated risk in T1D, prompting further investigation into additional factors. Emerging evidence suggests that metabolic dysfunction-associated steatotic liver disease (MASLD) plays a critical role in this heightened CVD risk. Objective: This narrative review aims to explore the relationship between MASLD and CVD in individuals with T1D. The review focuses on the prevalence of MASLD, its contributing risk factors, and the potential impact of liver dysfunction on cardiovascular outcomes in this population. Methods: A review of existing literature was conducted, focusing on observational studies, cohort studies, and meta-analyses that investigate the prevalence of MASLD in T1D populations and its association with CVD. The review also examines the physiological mechanisms linking MASLD and CVD, including insulin resistance, systemic inflammation, and hepatic dyslipidemia. Key studies were evaluated to identify patterns in MASLD prevalence based on diagnostic modalities and to assess the independent contribution of MASLD to cardiovascular risk in T1D patients. Conclusion: MASLD is increasingly recognized as a significant contributor to CVD in individuals with T1D, particularly in those with shared risk factors like obesity and insulin resistance. Evidence suggests that MASLD exacerbates hepatic and systemic metabolic dysfunction, increasing CVD risk through mechanisms such as chronic inflammation and atherogenic lipid profiles. Routine liver health assessments and tailored management strategies targeting MASLD should be incorporated into clinical care for individuals with T1D to mitigate long-term cardiovascular complications.